(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2022)
Studies have been developed to improve cultivation conditions through the introduction of beneficial compounds, among which are vitamins. The present work aimed to investigate the effects of the application of vitamins in the onion crop, cultivated in the conditions of the Cerrado biome. For that, five treatments were used, composed of different vitamins (ascorbic acid, thiamine, niacin and pyridoxine), in a concentration of 100 mg L-¹ and a control treatment, with water application, via foliar spray. The characteristics of chlorophyll relative index, number of plant leaves, plant height, fresh leaf mass, leaf dry mass, bulb diameter, bulb mass and bulb yield were evaluated. It was found that the application of ascorbic acid (AA) and pyridoxine (B6) increased the relative levels of chlorophyll concerning the control treatment and those composed by the application of niacin (B3) and thiamine (B1). In addition, for liquid photosynthesis, a superior result was shown when vitamins B3 and B1 were applied, concerning the other treatments. It was concluded that the exogenous application of vitamins alters the physiological and developmental behavior of onion plants, but does not positively affect bulb yield. The increases in photosynthetic activity were not reversed in bulb development, but in the elongation of plant leaves. Finally, the use of the vitamins studied for onion cultivation is not recommended, under conditions similar to those of the present study.